Association of parental knowledge, attitude, and practice of oral health with early childhood caries among preschool children: a systematic review - Alsharif, Mohammed Khalid Salim; Mohd Nazan, Ahmad Iqmer Nashriq; Ismail, Suriani (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Early childhood caries (ECC) is a serious public health problem in both developing and developed countries. Given that children mainly depend on their parents for their day-to-day activities, it is important to investigate the extent of parental influence on the oral health of their children. The objective of this study is to review the association of parental knowledge, attitude, and practice of oral health with ECC among preschool children. PubMed, Medline, and Google scholar were used to search for related articles published within the past 10 years. All of the studies that investigated parental oral health practice have shown association with the development of dental caries. However, there were discrepancies in the outcome of studies that examined the association of parental knowledge and attitude with ECC. More investigations on parental knowledge and attitude are needed to clarify their association with ECC.